Key account management practices: the importance of national cultures. The case of Sweden and Portugal - Garrido, Stéphane (2015)
The objective of current master thesis is to study the impact of cultural differences in key account management practices in Sweden and Portugal. To achieve that goal, the thesis starts with a theoretical background, followed by an empirical research and a conclusion at the end. The theoretical background discusses the essence of culture, the current cross-cultural studies, the cultural organization and the principles of key account management practices. The cultural dimensions compiled by Geert Hofstede are one of the core topics. In the light of it, a comparison between Sweden and Portugal is made using the cultural dimensions models. The fourth chapter introduces the empirical research and presents the results obtained from the quantitative research undertaken. The results from the survey differ to a certain extent from the cultural dimensions presented in the theoretical background. Furthermore, the findings of this thesis show some cultural differences when it comes to the way key account managers work with their key customers. Never mind, from all hypotheses only two were accepted. This means that even though it was possible to link to a certain extent the cultural dimensions from Hofstede to the questionnaire’s results, in the end the result was not the expected one. This may seem to imply that the organizational culture can sometimes be stronger than the cultural dimensions. Taking these findings into account, it is recommended that policies adopted by a multinational company should either be done for each country separately or providing total flexibility so it can be adapted locally.